2012
DOI: 10.1037/a0028273
|View full text |Cite
|
Sign up to set email alerts
|

Choice behavior of pigeons (Columba livia), college students, and preschool children (Homo sapiens) in the Monty Hall dilemma.

Abstract: In the Monty Hall dilemma, an individual chooses between three options, only one of which will deliver a prize. After the initial choice, one of the non-chosen options is revealed as a losing option, and the individual can choose to stay with the original choice or switch to the other remaining option. Previous studies have found that most adults stay with their initial choice, although the chances of winning are 2/3 for switching and 1/3 for staying. Pigeons, college students, and preschool children were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 35 publications
(71 reference statements)
5
26
2
Order By: Relevance
“…Although pigeons in the Switch group in Experiment 2 did switch more often than pigeons in the Stay and Control groups, their preference for switching was not as strong as has been previously observed (Herbranson and Schroeder, 2010;Mazur and Kahlbaugh, 2012;Stagner et al, 2013b). Finding individual variability in the MHD task is not uncommon, although the reduced preference for switching by pigeons in Experiment 2 may be due to the difference in the procedure.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…Although pigeons in the Switch group in Experiment 2 did switch more often than pigeons in the Stay and Control groups, their preference for switching was not as strong as has been previously observed (Herbranson and Schroeder, 2010;Mazur and Kahlbaugh, 2012;Stagner et al, 2013b). Finding individual variability in the MHD task is not uncommon, although the reduced preference for switching by pigeons in Experiment 2 may be due to the difference in the procedure.…”
Section: Discussioncontrasting
confidence: 43%
“…Although Stagner et al (2013a,b) found strong use of the switching strategy in pigeons, they did not replicate the exclusive usage of this strategy that Herbranson and Schroeder (2010) found; nor did Mazur and Kahlbaugh (2012). Much like Stagner et al (2013b), Mazur and Kahlbaugh (2012) found that pigeons switched about 60% of the time at Session 30.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, pigeons distributed a higher proportion of their responses to the higher-paying alternative than did humans in procedurally equivalent tasks (Goodie & Fantino, 1995Hartl & Fantino, 1996). Some research teams have reported that nonhuman animals appear to respond in a way that better maximizes payoffs than humans to probabilistic game-like tasks such as the Monty Hall Dilemma (e.g., Herbranson & Schroeder, 2010), although this is not always the case (e.g., Klein, Evans, Schultz, & Beran, 2013;Mazur & Kahlbaugh, 2012).…”
Section: Discussionmentioning
confidence: 93%